Endocytosis of GABA(C) receptors depends on subunit composition and is regulated by protein kinase C-? and protein phosphatase 1 - Linck, Lisa; Binder, Jasmin; Haynl, Christian; Enz, Ralf (Journal of Neurochemistry, 2015)
Neuronal excitability depends on the surface concentration of neurotransmitter receptors. Type C gamma-aminobutyric acid receptors (GABA(C)R) are composed of ? subunits that are highly expressed in the retina. Molecular mechanisms that guide the surface concentration of this receptor type are largely unknown. Previously, we reported physical interactions of GABA(C)R ? subunits with protein kinase C-? (PKC?) via adapter proteins of the ZIP protein family, as well as of protein phosphatase 1 (PP1) via PNUTS. Here, we demonstrate that co-expressing ?1 with ZIP3 and PKC? enhanced basal internalization of GABA(C)R, while receptor internalization was reduced in the presence of PNUTS and PP1. Co-expression of ?1 with individual binding partners showed no alterations, except for PP1. Heterooligomeric GABA(C)R composed of ?1 and ?2 subunits had a significant higher endocytosis rate than ?1 containing homooligomeric receptors. Mutant constructs lacking binding sites for protein interactions ensured the specificity of our data. Finally, substitution of serine and threonine residues with alanines indicated that GABA(C)R internalization depends on serine/threonine kinases and phosphatases, but not on tyrosine phosphorylation. We conclude that GABA(C)R internalization is reciprocally regulated by PKC? and PP1 that are anchored to the receptor via ZIP3 or PNUTS respectively.
EVALuna2:4723